"تأثير القبالة في فلسفة سبينوزا " - شباني منذر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
مارست القبَّالة Kabbalah , التسمية التي أطلقت على التصوف اليهودي منذ القرن الثاني قبل الميلاد تقريباً, دوراً مهماً على التراث اليهودي بشقيه الديني والفكري الفلسفي, دون أن يعني ذلك أن هناك فلسفة يهودية بعينها, بل أن ما نذهب إليه هنا هو البحث في تأثير القبَّالة على الفلاسفة من اليهود, وهم كثر, وسبينوزا الفيلسوف اليهودي السيفاردي، كان قد خضع لهذا التأثير بالوتيرة نفسها التي أثر فيها بالقبَّالة, وهو زعم ينشغل البحث في تقصي معالمه الأساسية ضمن ما أتيح من مصادر ومراجع عن القبَّالة, في محاولة للكشف عن انزياح القبَّالة من تصوف حلولي واحدي باتجاه ما عرف في تاريخ الفلسفة بمذهب وحدة الوجود (البانتيئية) وهو المذهب الذي أشارت إليه الأدبيات الفلسفية الغربية فيما هي تتعقب النشاط الفلسفي العقلاني لفلاسفة القرن السابع عشر, والتي وقفت طويلاً عند السبينوزية التي أفصحت عن نفسها بوصفها مذهب وحدة الوجود بالمعنى العريض لها. Kabbalah, the term given to Jewish mysticism ever since the 2nd Century BC., has had quite an impact on Jewish heritage, covering both religion and philosophical thought. However, we do not mean to suggest the existence of a Jewish philosophy per se. Rather, we intend to discuss the influence of Kabbalah on Jewish philosophers, and they are quite many. The claim that Spinoza, a Sephardim Jew, has influenced Kabbalah to the same degree that he has been influenced by it needs to be researched within the available literature we have on Kabbalah. This discussion will attempt to discover the Kabbalah shift of focus from monotheistic mysticism to what has later become known in the history of philosophy as pantheism, the attitude Western philosophical literature repeatedly referred to while it pursued the rational philosophical activity of the 17th Century. For a long time, this activity studied Spinozism which declared itself as the pantheism in its broadest sense.